PERSEPSI SISWA TENTANG KUALITAS MESIN JAHIT UNTUK PRAKTIKUM DI BENGKEL BUSANA BUTIK JURUSAN TATA BUSANA SMK N 8 PADANG - Rusda, Rusda; Nazar, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The aim this study is to describe of students’ perceptions about the quality of the sewing machines in terms of their damage and maintenance for worskshop in fashion boutiques laboratorium of SMKN 8 Padang. The typr of this research is quantitative descriptive, with 25% population from each local of dressmaking class at SMKN 8 Padang. Amount of sample total are 30 students. Taking sample used random sampling technique, mixed sample. The data processing was done by specifying and categorizing the percentage of observed items. The results of this study indicated that students’ prceptions about the quality of sewing machines reviewed from their damage is in the low category (59%) and the maintenance is in th good enough category (77,16%). For that reason, need to inprove the quality of sewing machines and their maintenance in order quality of them can support pactice learning at the clothing boutique of dressmaking programs at SMKN 8 Padang.Kata Kunci: Persepsi Siswa Tentang Kualitas Mesin Jahit